Let the people speak: improving regional adaptation policy by combining adaptive capacity assessments with vulnerability perceptions of farmers in Gujarat, India. (7th February 2019) - Stock, Ryan; Birkenholtz, Trevor; Garg, Amit
Abstract : Farmers throughout the Global South are vulnerable to extreme heat events and shifting precipitation patterns associated with climate change. This is particularly the case in Gujarat, India, which is experiencing fluctuating monsoon rains and seasons. Local institutions there are ill-equipped to assist farmers in adapting to these changes. However, farmers are adapting to climate change, largely through livelihood diversification, in the absence of formal state intervention. Using qualitative methods, we conducted adaptive capacity assessments and assessed vulnerability perceptions in 3 villages, involving 120 farmers from diverse socioeconomic backgrounds. Combining vulnerability perceptions with adaptive capacity assessments, we better observed the mismatch between rural development policy with the potential to aid in adaptation processes that address local needs, identifying why policy fails to increase the adaptive capacity of the agriculturalists most vulnerable to climate impacts. Decentralizing adaptation programmes to community-level institutions can increase the efficacy of climate interventions by emboldening latent institutions, while not widening the socioeconomic gap of a rapidly modernizing India.